Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.3389/fcell.2020.609290
|View full text |Cite
|
Sign up to set email alerts
|

High Dosages of Equine Chorionic Gonadotropin Exert Adverse Effects on the Developmental Competence of IVF-Derived Mouse Embryos and Cause Oxidative Stress-Induced Aneuploidy

Abstract: Gonadotropins play vital roles in the regulation of female reproductive ability and fertility. Our study aimed to determine the effects of superovulation induced by increasing doses of equine chorionic gonadotropin [eCG; also referred to as pregnant mare serum gonadotropin (PMSG)] on the developmental competence of mouse embryos and on aneuploidy formation during in vitro fertilization (IVF). eCG dose-dependently enhanced the oocyte yield from each mouse. Administration of 15 IU eCG significantly reduced the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 109 publications
(57 reference statements)
0
17
0
2
Order By: Relevance
“…At the blastocyst stage, we recorded a depletion of the inner cell mass under the same gonadotropin dosage (10 I.U.) as used in another study 15 , although the mouse strains were different. The depletion of epiblast and primitive endoderm cells echoes our previous work 71 , in which we reported on a small – but not negligible – proportion of non-manipulated, in vivo-produced blastocysts lacking epiblast cells in their inner cell masses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the blastocyst stage, we recorded a depletion of the inner cell mass under the same gonadotropin dosage (10 I.U.) as used in another study 15 , although the mouse strains were different. The depletion of epiblast and primitive endoderm cells echoes our previous work 71 , in which we reported on a small – but not negligible – proportion of non-manipulated, in vivo-produced blastocysts lacking epiblast cells in their inner cell masses.…”
Section: Discussionmentioning
confidence: 99%
“…Superovulated oocytes had reduced ability for endocytosis 11 and derivative blastocysts had fewer microvilli 12 than naturally ovulated counterparts, but ultrastructural differences were otherwise unimpressive. Some studies reported an increase of the rate of embryo aneuploidy and fetal malformation by use of gonadotropins [13][14][15][16][17] , while others contradicted these findings 4,18,19 . Some studies linked the superovulation to a direct effect on the acquisition of DNA methylation in oocytes [20][21][22][23][24] , including epimutations 25 , while…”
mentioning
confidence: 99%
“…At the blastocyst stage, we recorded a depletion of the inner cell mass under the same gonadotropin dosage (10 I.U.) as used in another study 14 , although the mouse strains were different. The depletion of epiblast and primitive endoderm cells echoes our previous work 72 , in which we reported on a small -but not negligible -proportion of non-manipulated, in vivo-produced blastocysts lacking epiblast cells in their inner cell masses.…”
Section: Discussionmentioning
confidence: 99%
“…Superovulated mouse oocytes had reduced ability for endocytosis 10 and derivative blastocysts had fewer microvilli 11 than naturally ovulated counterparts, but ultrastructural differences were otherwise unimpressive. Some studies reported an increase of the rate of embryo aneuploidy and fetal malformation by use of gonadotropins [12][13][14][15][16] while others contradicted these findings 4,17,18 . Likewise, while some studies linked the superovulation to a direct effect on the acquisition of DNA methylation in oocytes [19][20][21][22][23] , including epimutations 24 , other studies found no such effect 25,26 .…”
Section: Introductionmentioning
confidence: 99%
“…Barbara McClintock's Nobel Prizing winning research previously identi ed activation of retrotransposons as a response to stress [37]. A derivative hypothesis is that stress from ovarian hyperstimulation [38][39][40] and/or embryo culture activates transcription of L1. Our ndings that prolonged embryo culture increased L1 copy number are consistent with Professor McClintock's model.…”
Section: Discussionmentioning
confidence: 99%